Rituximab Efficacy in the Treatment of Children with Chronic Immune Thrombocytopenic Purpura. (1st September 2014) - Ansari, Sh.; Rostami, T.; Yousefian, S.; Kiumarsi, A.; Miri-Aliabad, G.; Ramim, T.
<x xml:space="preserve">Abstract</x> Background: There are several medications for treatment of immune thrombocytopenic purpura (ITP), including corticosteroids, intravenous immunoglobulin, immunosuppressive drugs, and even splenectomy. In case of failure, Rituximab as one of the medications used in these patients should be considered. Method: This Case—series study was conducted prospectively in patients who were referred to Hematology & Oncology Clinic of Ali Asghar Hospital. Eighteen Patients were followed up for at least 3–5 years. Results: Four weeks after treatment, only in 6 patients (33/3%) of 18 patients, complete response (Plt > 100, 000) were obtained and most patients (67/66%) had no appropriate response. In subsequent surveys conducted at 6 and 36 months after treatment, the percentage of patients responding fell to 22/2% hit. Conclusion: The results of this study demonstrate proper safety of Rituximab in the treatment of chronic ITP. However, the drug had no significant effect on the expected improvement in platelet count of patients. It seems that monotherapy is ineffective in the treatment of chronic ITP and combination with other complementary therapies is recommended.